Evaluating the efficiency and productivity of Vietnamese commercial banks: A data envelopment analysis and Malmquist index - Nguyen, Thi Hong Vinh (Đại học Kinh tế, 2016)
This paper provides a new evidence on the performance of twenty Vietnamese commercial banks over the period 2007-2010. The study used Data Envelopment Analysis to analyze the efficiency and productivity change of Vietnamese commercial banks. The results show that the efficiency of Vietnam commercial banks increased from 0.7 in 2007 to 0.818 in 2010. However, the results suggest that Vietnamese banks suffer slight inefficiencies during the global financial crisis in 2008. In addition, the results show the average annual growth of the Malmquist index 8.8 percent over the study period despite having dropped by 24.9 percent in 2009. These findings can help bank managers and government to understand banks’ efficiency performance and the underlying reasons of inefficiency.